Smallholder Farmers’ Adaptation Strategies and Food Security: Experiences from Zimbabwe - Nciizah, Tendai; Nciizah, Elinah; Mubekaphi, Caroline; Nciizah, Adornis D. (Springer, Singapore, 2022)
The reliance of African smallholder farmers on rain-fed agriculture exposes farmers to the deleterious effects of climate change. Climate change has become a tangible threat to agricultural production with negative effects on household food security. Frequent droughts in Africa have led to extremely low crop yields in crops and mortality of livestock. There are various strategies which have been identified to have potential to offset the negative impact of climate change within smallholder farmers’ conditions. Adaptation prepares farmers to adjust to current or future changes in climate thereby reducing their vulnerability to climate change. Prominent adaptation practices include shifting planting dates; adopting improved land management practices such as adopting tree planting, changing crop cultivars, zero tillage, and crop diversification. Despite these wide range of choices of adaptation strategies, smallholder farmers continue to get very low yields, thus resulting in food insecurity. This chapter discusses adaptation strategies used by smallholder farmers across Zimbabwe and their bearing on food security. In addition, the chapter also highlights key challenges faced by farmers in adopting these adaptation strategies and suggests new adaptation options that may address current gaps.